Lateral Torsional Buckling of Castellated Beams Analyzed using the Collapse Analysis. (2017) - Kwani, Sandhi; Wijaya, Paulus Karta
Abstract: In designing a steel beam, one of the limit states is lateral torsional buckling. The value of the bending moment limit is called the critical moment. AISC specification only provides formulas for calculating the critical moment in prismatic beams, but not for non-prismatic beams like castellated beams. The objective of this paper is to study the lateral torsional buckling of castellated beams. The method used for this study is the collapse analysis using the finite element method, analyzed by ADINA 8.9. In the collapse analysis, a geometrically imperfect beam is loaded with an increasing load. At a certain value of the load, the lateral displacement increases progressively. The value of the maximum load is considered to be the critical load. In this study, the imperfection is taken 1/1500 of the unbraced length of the beam. The critical moment of castellated beam obtained from the finite element analysis is up to 42.31% lower than the critical moment of full beams with the same dimension calculated by using the AISC formula. Therefore, the correction factor for AISC formula to calculate the critical moment of the castellated beam is established.